The museum and digital transformation: reforming national museums in Nigeria towards a new normal (Shanti Journal, 2024)
Nigeria is home to 53 National Museums, 65 National Monuments, and 2 world heritage sites. The development of information, communication, and technology (ICT) in the twenty-first century has led to a digital transformation of museums, with the use of digital tools in areas like virtual tours and visits, exhibitions, performances, concerts, and documentation, among others. Unfortunately, for a number of reasons that will be discussed in this paper, Nigeria is still falling behind in this age of digital transformation. This essay examines the history of museums and the idea of 21st-century digital change. It examines the numerous strategies that museums throughout the world have embraced in an attempt to draw in more visitors and maintain their financial viability over time. A comprehensive understanding of digital transformation requires an analysis of its drivers and constraints using a variety of theoretical frameworks. This study uses a qualitative method for data collection and analysis. The historical research design is applied in this study. Primary and secondary sources of data were gathered for this research study from books, journal articles, newspaper editorials, conference proceedings, magazines, websites, and new media are some of the resources that are used in the data collection process drawn from selected relevant museums, cultural agencies, literatures,curators, and scholars. The research comes to the conclusion that national museums must embrace a national model for digital transformation in order to transform digitally. This would ensure that the museum stays relevant in the twenty-first century while protecting its unique cultural legacy and help save a lot of jobs. Museum stakeholders were given recommendations based on strong evidence, with a special emphasis on Nigeria, about how to continue to be relevant in fostering meaningful debate in the era of digitization.